Interval hypoxic training modeling and efficiency rating - Byalovsky, Y. Y.; Lapkin, M. M.; Pokhachevsky, A. L.; Davydov, V. V.; Bulatetsky, S. V.; Voronin, R. M. (Theory and Practice of Physical Culture, 2018)
Individual physical working capacity and rehabilitation process efficiencies are determined by the hypoxic adaptation efficiency. Objective of the study was to rate the bodily oxygen debt process versus the hypoxic loads applied. Subject to the study were 57 healthy individuals of both sexes aged 22 to 42 years. The inspiration resistance respiratory loads (RL) were controlled by respiration simulator `BVD-01`. The sample was split up into the following three groups of 19 people each: Group 1 subject to hypoxic loads rated at 20% of the maximum and applied 3 times per 3min; Group 2 trained by uninterrupted 10-min hypoxic loads; and Reference Group 3. The hypoxic training micro-cycle was 10 days long. The lipid metabolism and catecholamine blood levels were tested on a daily basis prior to and after each training session. The study data were indicative of the 3-min RL being beneficial as it was found to effectively slow down the membrane oxidation and damaging process and improve the anti-oxidation protection mechanisms; whilst the 10-min RL yielded an opposite result. The membrane protecting effects of the short inspiration hypoxic loads tested in every subject irrespective of age and gender showed the adaptive responses being highly dependent on the hypoxic training process design and management.